IMPLEMENTASI TUGAS DAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) - Mawardi De La Cruz (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The purpose of this study was to determine the application of the principle of transparency in the delivery of local government in North Gorontalo Regency Gorontalo province as well as to determine the factors that affect the application of the principle of transparency. Application of the principle of transparency in local governance which has not run as mandated by Law No. 6 of 2014 on the village does not operate effectively. The factors that lead to ineffective application of the principle of transparency in local governance in North Gorontalo District are a lack of personnel resources and the limited facilities and infrastructure.